2009
DOI: 10.1007/s00330-009-1437-z
|View full text |Cite
|
Sign up to set email alerts
|

Fully automatic quantitative assessment of emphysema in computed tomography: comparison with pulmonary function testing and normal values

Abstract: Characterisation and quantification of emphysema are necessary for planning of local treatment and monitoring. Sensitive, easy to measure, and stable parameters have to be established and their relation to the well-known pulmonary function testing (PFT) has to be investigated. A retrospective analysis of 221 nonenhanced thin-section MDCT with a corresponding PFT was carried out, with a subgroup analysis in 102 COPD stage III+IV, 44 COPD stage 0, and 33 investigations into interstitial lung disease (ILD). The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
105
1
11

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(123 citation statements)
references
References 34 publications
6
105
1
11
Order By: Relevance
“…(7)(8)(9)(10)(11)(12)(13)(14)(15) The method has been recommended for use in longitudinal studies of emphysema and is currently considered to be better than functional tests for disease assessment. (6,16) In addition, previous studies have reported that the correlation between CT densitometry and macroscopic morphometry is higher than is that between macroscopic morphometry and subjective visual grading of emphysema.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(7)(8)(9)(10)(11)(12)(13)(14)(15) The method has been recommended for use in longitudinal studies of emphysema and is currently considered to be better than functional tests for disease assessment. (6,16) In addition, previous studies have reported that the correlation between CT densitometry and macroscopic morphometry is higher than is that between macroscopic morphometry and subjective visual grading of emphysema.…”
Section: Discussionmentioning
confidence: 99%
“…(6) Additionally, HRCT and helical CT can detect and quantify pulmonary emphysema, HRCT and helical CT findings correlating well with histopathological findings. (7)(8)(9)(10)(11)(12)(13)(14) Finally, modern CT scanners with multiple rows of detectorsmultidetector CT (MDCT)-allow the acquisition of thin (< 1-mm) slices of the whole chest in a few seconds, improving spatial resolution and avoiding respiratory artifacts.…”
Section: Introductionmentioning
confidence: 99%
“…26 However, because of concern regarding artifact from image noise and truncation artifact at the first percentile level, most studies have used the 15th percentile threshold. 30,31 It is important to remember that the measurement of the percentage of low attenuation areas (%LAA), while it correlates moderately well with histologic severity of emphysema (with r values between 0.5 and 0.6), is not a direct measurement of emphysema. The term percentage of emphysema (% emphysema) is widely used to refer to such CT measurements, but is imprecise and may give rise to confusion.…”
Section: Emphysemamentioning
confidence: 99%
“…In 2006, Madani et al (7) has shown the optimal HU threshold to be -960 HU or -970 HU according to macroscopic and microscopic pathologic correlations. However, because higher threshold values result in higher sensitivity to image noise, the most commonly accepted threshold value is -950 HU (8), with the percentage area of lung less than -950 HU (the emphysema index, or %LAA-950) being widely used to estimate the emphysema component in COPD patients (Fig. 1A, B) (9).…”
Section: Emphysema Quantificationmentioning
confidence: 99%
“…However, because of concerns regarding increased image artifacts and noise at the first percentile level, the 15th percentile threshold is most commonly used (8,10). The percentile index has been reported to be more robust for evaluating longitudinal variations in emphysema, and as being less sensitive to lung volume changes (8,11).…”
Section: Emphysema Quantificationmentioning
confidence: 99%